Texnologik ta’limini sun’iy intellekt bilan integrasiyalash (SCIENCE and SOCIETY, 2025)
This article explores the integration of technological education with artificial intelligence (AI) and examines both the challenges and opportunities involved. The study analyzes how AI tools – such as interactive simulators, educational robots, and virtual laboratories – can enhance the effectiveness of teaching and learning. The authors argue that AI technologies contribute to improving educational outcomes by facilitating personalized learning, supporting the teacher’s role, and simplifying complex educational tasks.